Resurrecting Empire: Western Footprints and America's Perilous Path in the Middle East by Rashid Khalidi (Boston: Beacon Press, 2004. 240 pages.) (American Journal of Islam and Society, 2005)
Written at a critical historical juncture of Arab-western relations, Khalidi’stext provides a refreshing and informed account of western intervention inthe Middle East. It stresses the catastrophic human and political consequencesof western colonial adventures in the region and the neglect of thishistorical experience by current American foreign policy decision makers.Although written primarily for a non-academic, American audience, it is auseful and important text on contemporary Middle East history.Accessible and highly readable, it provides insights into a series ofmajor issues currently relevant to the study of the Middle East: democracy, oil, Palestine, and Iraq. The first chapter provides an account of westerncolonialism’s social, political, economic, and cultural legacy wrought on theMiddle East. Beginning with a brief introduction to the American march towar with Iraq, the author establishes an approach employed throughout thetext: juxtaposing the historical western colonial experience with theAmerican invasion and occupation of Iraq. Locating western involvement inthe Middle East within the context of the Ottoman Empire’s decline, Khalidihighlights the differential systems of colonial rule imposed on the region.Throughout, he emphasizes the indigenous resistance to colonialism, thusarguing against Orientalist discourses of indigenous acquiescence and subservienceto the supposed benevolence of colonialist rule. Two importantpoints emerge: first, that the political structures imposed by the colonialregimes have persisted, and second, that the region’s political cultureremains deeply rooted in the anti-colonial experience. This experience –entirely conditioned through European involvement in the region – meantthat for many, the United States never experienced the same political andcultural hostility as Europe. Throughout the cold war, however, the UnitedStates’ image as a disinterested outside power began to give way to an imageof the United States as a significant power broker in the region with manyinterests, and, most importantly, few objectives compatible with the politicaldesires of the region’s peoples ...